1996
DOI: 10.1038/icb.1996.64
|View full text |Cite
|
Sign up to set email alerts
|

NK‐like activity against allogeneic tumour cells demonstrated in the spleen of control and thymectomized Xenopus

Abstract: Summary This paper addresses the issue of natural killer (NK) cell evolution by searching for NK-like activity in an amphibian representative, the immunologically well-characterized clawed frog. Xenopus laevis. Using in vitro 6 h -'chromium release assays, we have shown that splenocyte effectors from early thymectomized (Tx) year-old frogs, but not from control siblings, are able to spontaneously lyse allogeneic thymus tumour cell lines that lack MHC antigen expression. Such lytic capacity can be readily induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Other mAb created against lower vertebrate NK-like cells either fail to label (unpublished data) Xenopus lymphocytes (e. g. the anti-chicken NK mAb 28-4 [27]), or display inappropriate specificity [15] (e. g. the anti-fish NCC mAb 5C6 [8]). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other mAb created against lower vertebrate NK-like cells either fail to label (unpublished data) Xenopus lymphocytes (e. g. the anti-chicken NK mAb 28-4 [27]), or display inappropriate specificity [15] (e. g. the anti-fish NCC mAb 5C6 [8]). …”
Section: Discussionmentioning
confidence: 99%
“…Spleen, liver and gut lymphocytes were assayed directly ex vivo, or after 2 day preculture. Cells were cultured at 27°C in 5 % CO 2 in 24-well plates, at˚2 × 10 6 leucocytes/ml, in B 3 B 7 tumor cell medium [15] supplemented with 25 % GFM derived from ConA-stimulated X. laevis splenocytes, from which ConA had been removed [17].…”
Section: Preparation and Culture Of Lymphoid Cells From Spleen Livermentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, mammalian NK-cell receptors have expanded and diversified in a species-specific fashion, as in the case of KIR receptors in primates and Ly49/killer cell lectin-like receptors in rodents (Carrillo-Bustamante et al 2016). NK-like cells have been identified in nonmammalian species such as chicken (Jansen et al 2010), Xenopus (Horton et al 1996), and catfish, where spontaneous killing of allogeneic cells by non-TCR expressing cytotoxic cells was demonstrated (Shen et al 2004;Yoder 2004). A recent study using single-cell qPCR based on known markers of blood cell lineages revealed the presence of a small population of immune cells in zebrafish, which were proposed to represent putative NK-like cells based on expression of NK-lysin genes (Moore et al 2016).…”
mentioning
confidence: 99%